Analysis of Consumption and Productivity Patterns in Islamic Economics - Aiza Zulmairoh; Nur Umida; Yuliana; Zulfikar Hasan (Penerbit Hellow Pustaka, 2024)
Analysis of consumption and productivity patterns in the Islamic economy provides an in-depth understanding of how religious principles influence economic governance. Consumption in the Islamic economy is emphasized on the principles of justice, blessing and social responsibility, while productivity is directed at creating sustainable added value. Internal factors such as religion, culture, education, and economic status, as well as external factors such as price, product availability, government policies, and globalization, influence the consumption patterns and productivity of Muslim communities. Analysis based on Islamic economic principles shows the importance of practicing values ​​such as halal and haram, fairness and justice, moderation, and social welfare in economic activities to create a sustainable and ethical economy in Muslim society. based on sharia principles that are fair, sustainable , and oriented towards the welfare of the people. In conclusion, this analysis provides a comprehensive view of how Islamic economics can play an important role in shaping consumption and productivity patterns that benefit individuals, society and the environment.